Isu ‘Poket Development’ Membawa Kepada Masalah Banjir Kilat di Kawasan Pinggir Bandar - Ramli, Hanis Syazwani; Shafii, Haryati; Masram, Haidaliza; Ta Wee, Seow; Sarpin, Norliana; Ibrahim, Mohd Hairy (Research in Management of Technology and Business, 2023)
Issue of 'pocket development' occurs in almost all cities in Malaysia. The research problem for this study is the issue of "pocket development" that occurs in suburban areas leading to drainage system problems that cause flash flood disasters. Therefore, the objective of this study is to identify the factors of "pocket development" that lead to drainage system problems in suburban areas, analyse the impact of "pocket development" development on drainage system problems and contribute to flash floods in suburban areas and suggest alternative approaches which aims to deal with the effects caused by "pocket development". The research method used is a quantitative and qualitative approach. Questionnaire and interview methods were used to obtain the necessary information. Respondents for the questionnaire method are residents of Kampung Batu 5 Bangi, Semenyih Selangor. While the respondents for the semi-structured interview method were engineers from the Irrigation and Drainage Department (JPS) and the Director of the Development Planning Department at the Kajang Municipal Council (MPKJ). The results of the study were collected and analysed using the Statistical Package for Social Science (SPSS) and content analysis methods. According to the respondents' views, the "pocket development" factors that contribute to drainage system problems in suburban areas are dense development, unfriendly drainage systems, drain pollution and high rainfall intensity. As for the effects, the respondents are of the opinion that the rapid development causes the suburbs to become more and more squeezed in the current of urbanization, the drainage system is clogged because it is filled with litter and soil deposits that interfere with the flow of rainwater, the river's inability to accommodate rainwater capacity causes flash floods and incidents landslides due to uncontrolled land exploration activities. Among the methods of improvement that have been identified is deepening the river by digging mud and dirt in the river, drains and ditches must be well maintained, drainage management and drainage design must follow the standards that have been set and control human activities such as dumping rubbish and industrial waste into the river. By this, drainage system problems that often occur in urban areas can be successfully overcome for the well-being of the community and the environment.